The Translation Scene in Latvia (Latvian SSR) during the Stalinist Years - Veisbergs, Andrejs (Vertimo studijos, 2018)
[full article, abstract in English; abstract in Lithuanian] In this paper the author continues to explore the translation scene in 20th century Latvia (Veisbergs 2016a). The period under discussion covers 1945–1953, the years of Stalin’s rule after WWII until his death in 1953. The translation situation is described by discussing nationalisation and centralisation of publishers, book liquidation, censorship, ideologisation and politicisation, russification, Latvian émigré translations and other aspects of importance in an attempt to present the translation scene of the period from different angles. At the end of the article an extensive list of references is provided that can serve as an initial bibliography for more extensive research of translation practices in Latvia and beyond.